Carreiras em contextos de estudo e trabalho: barreiras, apoios sociais, enfrentamento e desfechos pelo modelo de autogerenciamento da teoria social cognitiva de carreira - Melo, Mariana Ramos de (2023)
This thesis aimed to verify how career barriers and social supports, in different environments, types and levels, distinctly impact individuals' adaptive coping behavior and career self-management, given a context of contextual crisis. Two sequential quantitative studies were based on social-cognitive career selfmanagement model (CSM; LENT; BROWN, 2013) of Social Cognitive Career Theory (SCCT). Study 1 aimed to verify the effect of contextual career barriers’ perceptions on functional coping strategies through self-efficacy expectations and emotional social support held by undergraduate students, given a context of contextual crisis. A survey was conducted among 163 brazilian senior undergraduate students attending Business and Administration areas. Data analysis included descriptive statistics, confirmatory factor analysis and mediation analysis. The main results revealed that analyzed contextual influences impact functional coping strategies in different ways. Barriers impacted only indirectly and social support impacted directly. It was also found that self-efficacy did not mediate the relationship between barriers and coping. Emotional social support played a mediating role in the relationship and was a predictor of self-efficacy in the serial mediation model. In turn, Study 2 aimed to test CSM applied to adaptive coping behavior in the face of contextual perceptions, social supports and career barriers held by undergraduate students and workers, given a context of contextual crisis. According to CSM, the variables included in test were contextual (career barriers and social support in family and at work), self-efficacy (occupational), actions (functional coping strategies) and outcomes (selfmanagement, career satisfaction, life satisfaction, employability). Additionally, volition at work was included in the MAC test. A survey was also conducted by two stages. Stage i included 261 brazilian undergraduate students attending Business and Administration areas. The objective was to develop detailed analyzes of relationships through mediation and moderation models. Data analysis included descriptive statistics, confirmatory factor analysis, mediation and moderation analysis. Results indicated that: a) self-efficacy and functional coping strategies are serial mediators that explain the relationship between social support at work and positive career outcomes; b) functional coping strategies mediate the relationship between social support in family and positive career outcomes; c) family social support of the material type moderates the relation of contextual career barriers and general restrictions, of the construct volition at work; and, d) family social support of the material type moderates the relationship of contextual career barriers and volition at work. Stage ii expanded the analyzes and included 566 brazilian undergraduate students attending different courses. The objective was to develop general analyzes of direct relationships through the joint test of the CSM. Data analysis included descriptive statistics, confirmatory factor analysis and Structural Equation Modeling. Results indicated compliance for the most part with MAC assumptions. However, contrary to what was expected, it was found that career barriers do not predict functional coping actions, and barriers and social supports do not predict some positive career outcomes. Based on the results, it was possible to support the argument of this Doctoral Thesis: in a scenario of contextual crisis, career barriers and social supports favor actions and positive career outcomes through mediation mechanisms and moderation conditionals. Briefly, the main theoretical contributions are: i) Perceived contextual barriers in the career can favor positive actions and failures in the career when they are related to social support through mediation or moderation; ii) Functional coping of contextual barriers perceived in career is based on the external environment; iii) Contextual influences related to supports and barriers can assume roles of predictors, mediators or moderators in relationships with self-efficacy, coping and positive career outcomes; iv) Career contextual barriers differ from volition at work and can be related to this through interaction with social supports; iv) CSM applied to adaptive coping behavior in the face of contextual perceptions is able to predict levels of functional coping and positive career outcomes among student-workers; and, vi) Volition at work can add explanatory power to MAC.